2014
DOI: 10.1200/jco.2013.54.2050
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Impairment in Older Patients With Breast Cancer Before Systemic Therapy: Is There an Interaction Between Cancer and Comorbidity?

Abstract: A B S T R A C T PurposeTo determine if older patients with breast cancer have cognitive impairment before systemic therapy. Patients and MethodsParticipants were patients with newly diagnosed nonmetastatic breast cancer and matched friend or community controls age Ͼ 60 years without prior systemic treatment, dementia, or neurologic disease. Participants completed surveys and a 55-minute battery of 17 neuropsychological tests. Biospecimens were obtained for APOE genotyping, and clinical data were abstracted. Ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
139
3
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 147 publications
(150 citation statements)
references
References 90 publications
2
139
3
6
Order By: Relevance
“…Cognitive decline over time raises the question of whether patients with cancer, particularly those who receive chemotherapy, may be at risk for accelerated cognitive aging. 18,19 Those with lower preexisting cognitive reserve are expected to be at greater risk 20,21 ; although our study did not show such an effect, it is confounded because those with less cognitive reserve were more likely to drop out. Longer follow-up is required to address this issue.…”
Section: Discussioncontrasting
confidence: 44%
“…Cognitive decline over time raises the question of whether patients with cancer, particularly those who receive chemotherapy, may be at risk for accelerated cognitive aging. 18,19 Those with lower preexisting cognitive reserve are expected to be at greater risk 20,21 ; although our study did not show such an effect, it is confounded because those with less cognitive reserve were more likely to drop out. Longer follow-up is required to address this issue.…”
Section: Discussioncontrasting
confidence: 44%
“…Third, older people with cognitive impairment are more frequently isolated (34), and turn away persons who want to help, to avoid facing their difficulties (35). Finally, it is increasingly reported that chemotherapeutic agents can worsen the patient's cognitive status (36)(37)(38). Thus, it is obvious those patients with cognitive impairment at the start of chemotherapy are more vulnerable, and that their vulnerability can be worsened by chemotherapeutic agents (39,40).…”
Section: Discussionmentioning
confidence: 99%
“…Patients with cognitive impairment should definitely be identified and steered towards rehabilitation and adapted care (38), including psychological support (35). More generally, health services should be adapted to the needs of this vulnerable population (need for services to be organized at the bedside and flexibility in scheduling appointments).…”
Section: Discussionmentioning
confidence: 99%
“…101 Evidence suggests that preexisting cognitive impairment, in many instances mild or subclinical, may be exacerbated during cancer treatment. 102 Therefore, a comprehensive cancer rehabilitation model that includes prehabilitation or pretreatment assessment should seek to establish a cognitive baseline to optimize proactive screening. 103 …”
Section: Cognitive Performancementioning
confidence: 99%